Baseline survey of sexually transmitted infections in a cohort of female bar workers in Mbeya Region, Tanzania. Issue 5 (22nd October 2003) - Riedner, G; Rusizoka, M; Hoffmann, O; Nichombe, F; Lyamuya, E; Mmbando, D; Maboko, L; Hay, P; Todd, J; Hayes, R; Hoelscher, M; Grosskurth, H
Abstract : Objectives: To determine baseline prevalence of sexually transmitted infections (STI) and other reproductive tract infections (RTI) and their association with HIV as well as sociodemographic and behavioural characteristics in a newly recruited cohort of female bar workers in Mbeya Region, Tanzania Methods: 600 female bar workers were recruited from 17 different communities during September to November 2000 and underwent gynaecological examination, laboratory testing for HIV/STI, and interviews using structured questionnaires. Results: HIV-1 seroprevalence was 68%. Prevalences of STI/RTI were high titre syphilis (TPPA/RPR ⩾1/8), 9%; herpes simplex virus 2 antibodies, 87%; chlamydia, 12%; gonorrhoea, 22%; trichomoniasis, 24%; and bacterial vaginosis, 40%. HIV infection was associated with TPPA and HSV-2 seropositivity, bacterial vaginosis and clinically diagnosed genital ulcers, blisters, and warts. Reported high risk sexual behaviour during the past year (having multiple casual partners) was associated with prevalent STI. Conclusion: Female bar workers in Mbeya are at high risk of STI and HIV infection. Targeted STI/HIV prevention interventions for these women and their sexual partners need to be reinforced. Methods should be sought to improve healthcare seeking and to provide easily accessible and affordable STI care services.